A facilely controlled length, cytotoxicity, length-dependent and cell type-dependent cellular uptake of silica nanotubes and their applications in the delivery of immunostimulatory CpG oligodeoxynucleotides1. Issue 36 (28th September 2015) - Chen, Song; Zhang, Qiqing; Jia, Lan; Du, Xinxin; Hanagata, Nobutaka
<x xml:space="preserve">Abstract</x> Silica nanotubes were synthesized via an acid-degradation collagen template route and then functionalized with chitosan to deliver immunostimulatory CpG-ODN.